Pertanggungjawaban Direksi Atas Tindak Pidana Perpajakan Ditinjau dari Doktrin Business Judgement Rule - Frisca Delicia, Nadya; Gunadi, Ariawan (Universitas Ekasakti, 2023)
Legislation in Indonesia is coercive and all-embracing. The tax sector is no exception. Both individuals and corporate entities have an obligation to pay taxes. As a taxpayer, it cannot be denied that there are opportunities to commit tax crimes. This article aims to analyze tax evasion as a means of tax crimes committed by company directors when viewed from the business judgment rule doctrine. This research uses normative juridical legal research by collecting secondary data. The results of this research show that directors can be held personally responsible if they are proven to have committed tax evasion on behalf of the company and cannot be protected by the business judgment rule doctrine.